(untitled) (Research, Society and Development, 2021)
The “teaching assistants” are directly active in higher education structures in Brazil and in other institutions around the world. They carry out activities closely to students, especially regarding to the enhancement and support of their learning, acting as intermediaries and advisers in the relationship between students and teachers. In this sense, this article presents an overview on the performance and attributions of the so-called teaching assistants in higher education around the world according to literature, discussing and analyzing their insertion in these structures and also what is the perception of the students about it. Being a qualitative research, through a literature review related especially to higher education, aspects related to general concepts and main benefits and challenges inherent to the profession are discussed, also bringing a comparison between the national scenario and that highlighted by different authors. In general, the literature evidences a mostly positive perception about teaching assistants in their work, being considered as facilitators of learning in many subjects of academic interest through the performance of practical functions and consistent with academic proposals. Among the main challenges of its performance are the low experience inherent in some situations, which sometimes makes it difficult to guide and contact students, and inclusive education that is not yet present frequently in academic environments of higher education in general.